National human rights institutions in Southeast Asia selected case studies - Gomez, James; Ramcharan, Robin (Human rights in Asia, 2020)
This book reviews Southeast Asia's National Human Rights Institutions (NHRIs) as part of an emerging assessment of a nascent regional human rights architecture that is facing significant challenges in protecting human rights.